1998
DOI: 10.1136/bmj.316.7144.1563
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of treatments for infantile colic: systematic review

Abstract: Objective: To evaluate the effectiveness of diets, drug treatment, and behavioural interventions on infantile colic in trials with crying or the presence of colic as the primary outcome measure. Data sources: Controlled clinical trials identified by a highly sensitive search strategy in Medline (1966-96), Embase (1986-95), and the Cochrane Controlled Trials Register, in combination with reference checking for further relevant publications. Keywords were crying and colic. Study selection: Two independent assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
1
29

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(242 citation statements)
references
References 46 publications
3
209
1
29
Order By: Relevance
“…Our findings show that infants fed with a partially hydrolysed formula, added with a mixture comprising 90% GOS and 10% FOS, had a significant decrease in colic episodes after 1 week of treatment compared to infants from the control group, confirming data of a previous observational study (Savino et al, 2003) and according to most of the diet studies on infantile colic (Lucassen et al, 1998(Lucassen et al, , 2000Garrison and Christakis, 2000). The difference in crying time was even more significant after 2 weeks of treatment.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings show that infants fed with a partially hydrolysed formula, added with a mixture comprising 90% GOS and 10% FOS, had a significant decrease in colic episodes after 1 week of treatment compared to infants from the control group, confirming data of a previous observational study (Savino et al, 2003) and according to most of the diet studies on infantile colic (Lucassen et al, 1998(Lucassen et al, , 2000Garrison and Christakis, 2000). The difference in crying time was even more significant after 2 weeks of treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Randomized controlled study for infantile colic F Savino et al symptoms (Miller-Loncar et al, 2004): Lucassen, in a recent review, reported that infantile colic should be treated preferably with a 1-week trial of a hypoallergenic formula (Lucassen et al, 1998). On the other hand, as Garrison suggested the need of further studies on existing and alternative dietary therapies (Garrison and Christakis, 2000), our study could represent a first step approaching colic from changing the feeding formula.…”
Section: Molecular Weight Distribution (Kda ¼ Kilodalton)mentioning
confidence: 80%
See 2 more Smart Citations
“…The benefit of cow's milk elimination has been shown in several studies, 12,13 and a 1-week trial with a hypoallergenic formula has been suggested for colicky infants. 14 However, no consensus about the role of cow's milk allergy or intolerance in colic has so far been reached. Parental counseling is beneficial 15,16 and is considered important in the current management of colic.…”
mentioning
confidence: 99%